SUBCONSCIOUS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article explains in detail what the subconscious is, how to use it and how to apply it in our lives and the miraculous changes that follow. In this article, we will get acquainted with the opinions expressed by several scientists about the subconscious.